Accounting for the Rigidity of Japan’s Nuclear Energy Policy - Takao, Yasuo (2019)
© 2019, © 2019 Japanese Studies Association of Australia. This article examines the seven decades since the end of World War II and the evolution of Japan’s nuclear energy policy from the perspective of both domestic/international structures and coalition building processes. The objective is to identify the causal mechanism that has produced the rigidity of today’s Japanese nuclear energy policy. This study takes an analytically eclectic approach. Viewing the single puzzle of policy rigidity through two different lenses, political opportunity structures and advocacy coalition framework accounts for different facets of Japan’s nuclear energy policy. This approach can also connect otherwise contending frameworks together to reveal factors in the policy rigidity of nuclear energy.